The impact of utilizing the Quran evidences in collecting the subject of The Islamic Arabic History and heading towards them by 2nd year intermediate students - Resan, Ahmad Niima (Al-Adab Journal, 2018)
The present research aims to identify the impact of the use of Quranic evidence in the collection of Arab Islamic history and towards it among second grade students. In order to achieve this, the researcher adopted a experimental design in the field of experimental designs with partial control. The sample consisted of 64 students, (B) to represent the experimental group, which is taught in the Quranic test method (32) students and (d) to represent the control group, which is taught in the traditional way The researcher conducted the equivalence between the two research groups, and the statistical results proved the parity of the two groups. The researcher formulated the behavioral goals for the research subjects and prepared the teaching plans, the test and the measurement of the direction, and then presented them all to the experts and verified the truthfulness and consistency and applied the final achievement test, Data processing statistically, there is a difference of statistical significance for the benefit of the experimental group, and accordingly the researcher made a number of suggestions and recommendations.